Does the number of drain tubes influence the formation of postoperative spinal epidural hematoma following biportal endoscopic unilateral laminotomy for bilateral decompression (BE-ULBD) in patients with two-level adjacent lumbar spinal stenosis? a prospective randomized study - Zhuolin Zhong; Jingjing Ying; Shaohua Zhang; Kaili Cai; Xiaowei Jing; Zhengyu Xu; Lejian Jiang; Tianxin Wu; Guojun Wei; Qingfeng Hu (Journal of Orthopaedic Surgery and Research, 2025)
Abstract Background The formation of postoperative spinal epidural hematoma (POSEH) following lumbar spinal surgery is a potentially serious complication. The efficacy and necessity of prophylactic postoperative drain tubes in preventing symptomatic postoperative spinal epidural hematoma (SPOSEH) after lumbar spinal decompression remain subjects of ongoing debate. The objective of this study is to investigate the potential impact of the number of drain tubes on POSEH following biportal endoscopic unilateral laminotomy for bilateral decompression (BE-ULBD) in patients of two-level adjacent lumbar spinal stenosis. Methods A prospective randomized study was conducted involving 89 patients with two-level adjacent lumbar spinal stenosis who underwent BE-ULBD. Patients were divided into two groups: Group A (one drain tube) and Group B (two drain tubes). Demographic data were collected, including preoperative visual analog scale (VAS) scores for leg pain and preoperative blood pressure (BP). Postoperative BP was recorded. The primary outcome was the cross-sectional area (CSA) of POSEH assessed at 72 h postoperatively. Secondary outcomes included postoperative VAS scores for leg pain, volume of drainage output, and length of hospital stay. Results A total of forty-three patients were assigned to Group A, while forty-six patients were assigned to Group B. The demographic characteristics of the patients in both groups were comparable. No significant differences were observed between the two groups regarding the CSA of POSEH. However, a significantly greater volume was noted in Group B (P = 0.015). There were no significant differences between the groups for other secondary outcomes, including postoperative VAS scores for leg pain (P = 0.584), and length of hospital stay (P = 0.428). Conclusions More drain tubes may result in statistically significant output but not clinically significant differences in influencing the formation of POSEH following BE-ULBD for two-level adjacent lumbar spinal stenosis. Trial registration The study was retrospectively registered in ClinicalTrials.gov on March 1, 2024, with the registration number NCT06290791.